From Academic to Professional English: Investigating Learning Transfer Between EAP and ESP Courses - Wang, Feiya; Xiao, Yangyu (Social Education Research, 2025)
The current study explores the learning transfer between English for Academic Purposes (EAP) and English for Specific Purposes (ESP) courses at an international university in China. Drawing on qualitative data from semi-structured interviews with 11 science and engineering students, the research explores academic skills transferred from the EAP to ESP courses and factors that affect such transfer. The findings revealed five key categories of transferred skills: research skills (e.g., logical thinking and literature reading), speaking skills (e.g., public speaking and presentation skills), language skills (e.g., appropriate vocabulary use and writing as a process), confidence, and time management skills. Factors affecting the transfer were classified as task-related (e.g., task type and difficulty), personal factors (e.g., personal interest and learning methods), and course-related (e.g., similarities and differences between EAP and ESP courses, as well as cross-disciplinary differences). This study enhances the understanding of learning transfer in EAP and ESP contexts and provides strategies for improving English language instruction for academic and professional purposes. Our findings suggest that EAP course design should emphasize higher-order skills and facilitate the transfer of academic literacies across disciplinary contexts.